Anterior or posterior walkers for children with cerebral palsy? A systematic review. (19th May 2018) - Poole, Marilyn; Simkiss, Doug; Rose, Alice; Li, François-Xavier
Abstract: Objective: To review the literature comparing use of anterior and posterior walkers (PW's) by children with cerebral palsy (CP) to determine which walker type is preferable. Methods: Electronic databases were searched using pre-defined terms by two independent reviewers. Reference lists of included studies were hand searched. Studies published between 1985 and 2016 comparing use of anterior and PW's by children with CP were included. All study designs and outcomes were accepted. Risk of bias was assessed using the "Quality assessment standard for a cross-over study". Quality of evidence was evaluated using GRADE. Results: Six studies were analysed. All studies had small sample sizes. A total of 4/6 studies were randomized. A total of 4/6 had high risk of bias. Outcomes included velocity, pelvic tilt, hip flexion, knee flexion, step length, stride length, cadence, double stance time, oxygen cost and participant/parental preference. Velocity, trunk flexion/pelvic tilt, and stability may be improved by using a PW, however, GRADE quality was very low for all outcomes and there was heterogeneity between studies. The majority of participants and parents preferred the PW. Conclusions: Heterogeneity and low quality of existing evidence prevented recommendation of one walker type. Well-designed studies with adequate power are needed to inform clinical recommendations. Implications for rehabilitation: Clinical recommendations cannot be made for whether anterior or posterior walkers are preferable for children with cerebral palsy based on the existing evidence. Velocity, trunk flexion/pelvic tilt, and stability may be improved by using a posterior walker. The majority of walking aid users and their parents preferred posterior walkers. Adequately powered studies designed to minimize bias are needed.